Pengaruh Effective Tax Rate Terhadap Profitabilitas pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Nugroho, Azka Aqil; Hariyati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of the Effective Tax Rate (ETR) on the profitability of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The study uses a quantitative approach with secondary data obtained from the companies' annual reports and financial statements. The research sample was selected using a purposive sampling technique based on the criteria of Consumer Non-Cyclicals companies listed consecutively on the IDX during the study period, publishing complete financial reports, and having the data necessary to measure the research variables. The independent variable in this study is the Effective Tax Rate (ETR), which is calculated by comparing the tax burden with profit before tax, while the dependent variable is profitability, measured using Net Profit Margin (NPM). Data analysis was performed using simple linear regression to test the effect of ETR on company profitability. The results showed that ETR had a significant effect on profitability with a significance value of 0.007 (<0.05) and a t-test value of 2.766. The direction of the effect indicates that an increase in ETR tends to be followed by a decrease in company profitability, because a larger tax burden can reduce the company's net profit. This finding shows that tax burden management is one of the factors that companies need to pay attention to in maintaining profitability levels